The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41746-021-00385-9
|View full text |Cite
|
Sign up to set email alerts
|

Do as AI say: susceptibility in deployment of clinical decision-aids

Abstract: Artificial intelligence (AI) models for decision support have been developed for clinical settings such as radiology, but little work evaluates the potential impact of such systems. In this study, physicians received chest X-rays and diagnostic advice, some of which was inaccurate, and were asked to evaluate advice quality and make diagnoses. All advice was generated by human experts, but some was labeled as coming from an AI system. As a group, radiologists rated advice as lower quality when it appeared to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
134
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(182 citation statements)
references
References 42 publications
9
134
5
1
Order By: Relevance
“…To our knowledge, this is the first prospective study of a deployed machine learning-based bedside clinical tool that quantitatively studies and achieves high provider adoption. Previous studies of deployed systems have used post-hoc surveys or interviews to gauge provider impressions 25,36,43 ; however, provider impressions can differ from their actual use 4,18,24 . A common alternative is to study real-time provider response using a clinical simulation 23,24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first prospective study of a deployed machine learning-based bedside clinical tool that quantitatively studies and achieves high provider adoption. Previous studies of deployed systems have used post-hoc surveys or interviews to gauge provider impressions 25,36,43 ; however, provider impressions can differ from their actual use 4,18,24 . A common alternative is to study real-time provider response using a clinical simulation 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Adoption of automated systems in non-clinical settings depends on several factors including personal characteristics and preferences of the user, characteristics of the automated system (e.g., CDS tool), and the environment in which the technology is used 22 . In clinical simulations in a 'laboratory' setting, where providers are shown simulated CDS recommendations for exemplar patients, studies have found that interface design 23 , provider expertise 24 , and clinical time constraints 25 all play a role in adoption of the tool. However, in the real-world clinical setting, there are additional barriers to system adoption, including unpredictable variations in workflow, changes in personnel, and high-stakes consequences of incorrect decisions, that are difficult to replicate in simulations 26 .…”
mentioning
confidence: 99%
“…We will envision strength training and sports management to follow the advances in medicine and society as a whole, with the trend for increased human-machine interplay in human-inthe-loop systems, that are developed augmenting human experts rather than by replacing them with AI [49,258,279,310,615,742,753]. It is not trivial to transfer and quantify the tacit knowledge from athlete-coach to be used for quantitative modelling [81,482,588], and the n = 1 expert knowledge [364,379,716,750];…”
Section: Precision Strength Trainingmentioning
confidence: 99%
“…Would the advice of ASTRO-X be considered in the diagnosis? These are all questions that the AI Contents lists available at ScienceDirect EBioMedicine journal homepage: www.elsevier.com/locate/ebiom community is dealing with for many newly developed deep learning models [8].…”
mentioning
confidence: 99%
“…Would the advice of ASTRO-X be considered in the diagnosis? These are all questions that the AI community is dealing with for many newly developed deep learning models [8] .…”
mentioning
confidence: 99%